FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS (STUDI EMPIRIS PADA BANK-BANK UMUM YANG TERCATAT DI BEI, PERIODE 2010 â 2017) - Adzani1, Nurul; Effendi, Maya Syafriana; Rismita, Rismita (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2018)
The research aims to find out the influence of CAR, BOPO, NIM and LDR to the ROA of commercial banks which are listed in Indonesia Stock Exchange period 2010-2017. The data used in this study was obtained from the Annual Financial Statements Bankings Companies listed on the Stock Exchange. After passing through the stage of purposive sampling , the samples are fit for use by 30 banking companies. The analysis method used the analysis of panel data regression with the help of Eviews 9.0. Panel data regression model is the regression model using panel which is a combination of cross section data and time series data. To estimate the panel data regression model, the are three approaches, those are common effect model, fixed effect model and random effect model. The result of panel data analysis shows that the appropriate panel data regression model for these data is the fixed effect model with cross section (no heteroscedasticity). Based on the research it has been found that the variables CAR and BOPO are negative and has significant impact on ROA. Meanwhile, the variables NIM and LDR are positive and has significant impact on ROA. Of the four significant variables, the variable NIM has the greatest influence on ROA with the coefficient of 0.201844. The result of the degree of determination (Adjusted R-square) in the regression model is equal to 0.937245. This shows that the effect of the independent variables, namely CAR, BOPO, NIM and LDR to the dependent variable (ROA) is 93.72% while the remaining 6.28% is effected by other factors which were explained in this research.